Assisted conception in women of advanced maternal age. (January 2021) - Seshadri, S.; Morris, G.; Serhal, P.; Saab, W.
Abstract: A delay in childbearing to later in life has increased the number of women of advanced maternal age (AMA) opting for assisted reproduction. Women should be made aware that there are age-related changes to fertility, including a decline in oocyte reserve and quality, in addition to an increase in the number of oocyte chromosomal aberrations. Success rates of assisted reproductive technology (ART) cycles decrease with advanced maternal age. There are different fertility options for women of AMA, including fertility preservation (oocyte or embryo freezing), in vitro fertilisation (IVF treatment) with or without preimplantation genetic screening and oocyte or embryo donation. Detailed counselling needs to be offered to these women with regard to the risks, success rates, ethical and legal implications of these fertility treatment options. Women of AMA should be screened for underlying medical conditions that could have an impact on maternal and neonatal morbidity and mortality. Highlights: Success rates of ART cycles are maternal age-dependent, reducing above of 35 years of age. There is a natural decline in ovarian reserve and quality in women of AMA. In women over 40 years, more than 50% of cycles of IVF result in poor ovarian response or cancellation. Social egg freezing may be offered to women at an earlier age provided they are counselled about the pregnancy rates using frozen eggs. PGT-A with IVF may be cost-effective, reduce the risk of clinical miscarriage, failed ART cycles, and may increase pregnancy rates in women above the age of 35.